Sociedades del conocimiento como motor generador de tecnología e innovación agrícola en el Ecuador - Mayorga Villamar y Colls., Carmen (2018)
The present study aims to analyze the contribution that produces knowledge societies as generator of technologies and innovations in the agricultural sector of the Republic of Ecuador. This contribution originates network evolutions in corporate and individual agricultural framework, through the design of new production processes and quality management processes and redesigning processes already used, which involve social and economic aspects in the context of ecuadorian agriculture. Based on propositions that knowledge societies of high scientific agricultural impact, contribute to improve the agricultural sector through the creation of new technologies and innovations directed to the ecuadorian agricultural system characteristics allowing a social, economic and growth in Ecuador. We must determine the term of "knowledge societies", in used in this research, considering it as a factor of social change in the expansion of education, and specific skills of employees, projecting a vision of educational efforts and training. Earlier in Ecuador, institutions that invested in knowledge societies as a source of scientific research to the agricultural process were private companies, while the public sector performing agricultural improvement, but low impact, due to the high cost that generates agricultural development programs for a country with efficiency, control and monitor. The beneficiaries of those programs reach the large and medium producers who are the owners of the most productive land in the country, leaving you vulnerable to small farmers. This has meant that in recent years , the results as a contribution to rural development have not been sufficient , showing high levels of poverty and decreasing endogenous development in the agricultural sectors , because the generated effects have not been useful for the farmer , corporate producers , processors, traders and agricultural exporters. The methods and techniques used in this scientific work are of theoretical knowledge, such as historical and logical, inductive-deductive, analysis-synthesis for analysis of knowledge societies generating technologies and innovation in the agricultural sector Ecuador, between the empirical methods of knowledge: scientific observation to study the fundamental characteristics of the agricultural sector and the contribution of knowledge societies. The techniques used are informative and argumentative documentary techniques of field. We conclude that this research will serve to knowledge societies through the creation of agricultural innovation technologies and raise the level of development in the productions, but contribute to industrial development, that Ecuador is introduced in market competition internal and external bracing a growing economic and social development.